Primary School Pupils' Use of Verb Collocations in Science Assessment: Patterns of Linguistic Behaviour by Language Background Factor - Míriam Buendía-Castro; Oksana Afitska (MDPI AG, 2023)
This article explores patterns of linguistic behaviour and challenges associated with low(er) linguistic competences in primary school learners in subject-specific areas of the curriculum. The study draws on science test data, specifically on two assessment tasks, collected from 209 primary school students, aged between 9 and 11 years (Key Stages 5 and 6 of the statutory framework for learning in England). The population sample is made up of learners from six state primary schools in Yorkshire and the Humber Region, UK. Some of the learners speak English as their mother tongue while others speak English as their second or third language. Learner test data were analysed in order to answer the following research questions: (1) What verb collocations do learners use when demonstrating their content knowledge on the topic of "separating solids and liquids" in Science? (2) Do English language learners (ELLs) and English native speaking learners (ENSs) use verb collocations differently? If so, what is the nature of these differences? The results revealed differences between linguistic performances in the two groups of learners. ENSs tended to produce natural collocations with motion verbs. ELLSs, however, faced challenges in producing idiomatic language. They also encountered more difficulties than ENSs in understanding assessment tasks' instructions and/or in reporting subject-specific knowledge in response to the assessment tasks.